2007
DOI: 10.1002/tox.20241
|View full text |Cite
|
Sign up to set email alerts
|

Light‐induced cytotoxicity of 16 polycyclic aromatic hydrocarbons on the US EPA priority pollutant list in human skin HaCaT keratinocytes: Relationship between phototoxicity and excited state properties

Abstract: The photocytotoxicity of 16 polycyclic aromatic hydrocarbons (PAHs) on the priority pollutant list of the United States Environmental Protection Agency (US EPA) were tested in human skin HaCaT keratinocytes. A selected PAH was mixed with HaCaT cells and irradiated with a solar simulator lamp for a dose equivalent to 5 min of outdoor sunlight and the cell viability was determined immediately and also after 24 h of incubation. For the cells without incubation after the treatments, it is found that all PAHs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 56 publications
(58 reference statements)
3
32
0
Order By: Relevance
“…The relative photocytotoxicity is: 1-HP ~ 1-AP ~ Pyrene > 1-BP > 1-NP. These results are similar to the previously reported in both HaCaT and Jurkat cells using some of the similar compounds 2,36,37 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The relative photocytotoxicity is: 1-HP ~ 1-AP ~ Pyrene > 1-BP > 1-NP. These results are similar to the previously reported in both HaCaT and Jurkat cells using some of the similar compounds 2,36,37 .…”
Section: Discussionsupporting
confidence: 92%
“…Co-exposure to pyrene and light irradiation causes human skin keratinocyte cells to become non-viable in a pyrene dose dependent manner 2 . It is suggested that damages to cellular constituents DNA, protein and lipids are the main reasons leading to phototoxicity 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Photodegradation of PAHs may be due in addition to UVA rays as well as visible light, and this is especially true in the case of PAHs with a higher content of aromatic rings, which are photosensitized upon radiation with a wavelength >400 nm [32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…The cell culture method was reported in a previous publication [30, 31]. After the HaCaT cells grew to a concentration of no less than 1×10 5 cells/mL, the cells were harvested and centrifuged at 2000 rpm for 5 min.…”
Section: Methodsmentioning
confidence: 99%